A Qualitative Study on the Transition Support Needs of Indigenous Australians Following Traumatic Brain Injury. Issue 2 (22nd August 2019) - Fitts, Michelle S.; Bird, Katrina; Gilroy, John; Fleming, Jennifer; Clough, Alan R.; Esterman, Adrian; Maruff, Paul; Fatima, Yaqoot; Bohanna, India
Abstract: Objective: A growing body of qualitative literature globally describes post-hospital experiences during early recovery from a traumatic brain injury. For Indigenous Australians, however, little published information is available. This study aimed to understand the lived experiences of Indigenous Australians during the 6 months post-discharge, identify the help and supports accessed during transition and understand the gaps in service provision or difficulties experienced. Methods and Procedure: Semi-structured interviews were conducted at 6 months after hospital discharge to gain an understanding of the needs and lived experiences of 11 Aboriginal and Torres Strait Islander Australians who had suffered traumatic brain injury in Queensland and Northern Territory, Australia. Data were analysed using thematic analysis. Results: Five major themes were identified within the data. These were labelled 'hospital experiences', 'engaging with medical and community-based supports', 'health and wellbeing impacts from the injury', 'everyday living' and 'family adjustments post-injury'. Conclusions: While some of the transition experiences for Indigenous Australians were similar to those found in other populations, the transition period for Indigenous Australians is influenced by additional factors in hospital and during their recovery process. Lack of meaningful interaction with treating clinicians in hospital, challenges managing direct contact with multiple service providers and the injury-related psychological impacts are some of the factors that could prevent Indigenous Australians from receiving the supports they require to achieve their best possible health outcomes in the long term. A holistic approach to care, with an individualised, coordinated transition support, may reduce the risks for re-admission with further head injuries.